2007
DOI: 10.1002/ar.20513
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pennate muscle architecture after gradual tibial lengthening in goats

Abstract: The purpose of this investigation was to examine the changes in unipennate muscle architecture after distraction osteogenesis. Nine adult goats underwent 20% tibial lengthening in one of the hind limbs. Immediately after distraction, lengthened and contralateral (untreated) tibialis caudalis (TC) muscles were harvested. Lengths of the muscle belly, muscle fiber (FL), sarcomere (SL), tendon (TL), and superficial aponeurosis, as well as muscle mass, pennation angle (PA), and physiological cross-sectional area (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…Increased sarcomere lengths, rather than sarcomere numbers, have been observed in a few studies, indicating that adaptation to the overstretch may have been incomplete or partially unsuccessful [84,85]. Failure of a muscle to properly adapt to the overstretch it experiences may result in contracture, or insufficient muscle length [85].…”
Section: Muscle Physiology Of Adaptationmentioning
confidence: 99%
“…Increased sarcomere lengths, rather than sarcomere numbers, have been observed in a few studies, indicating that adaptation to the overstretch may have been incomplete or partially unsuccessful [84,85]. Failure of a muscle to properly adapt to the overstretch it experiences may result in contracture, or insufficient muscle length [85].…”
Section: Muscle Physiology Of Adaptationmentioning
confidence: 99%
“…Limb lengthening by distraction osteotomy has become a routine surgical procedure and studies in goats have shown that it is the muscle rather than the tendon that provides the extra length within the muscle–tendon unit necessary for proper limb function. While the muscle may elongate by almost 10% of its initial length, the tendon only does so by 3–4% (Elsalanty et al. 2007).…”
Section: Elastic Recoil Of Tendonsmentioning
confidence: 99%
“…Toutes les études ne montrent pas d'augmentation du nombre de sarcomères en série après un programme d'étirement. Certaines d'entre elles ont montré que la longueur des sarcomères pouvait augmenter à la suite de protocoles d'étirement sur modèle animal [49,50]. De tels résultats ont tendance à suggérer que la réponse initiale des muscles aux étirements est l'augmentation de la longueur de sarcomère, mais quand un seuil global d'étirement est atteint, alors de nouveaux sarcomères sont disposés en séries.…”
Section: Durée Des Adaptationsunclassified